Reiteration in Short Story and its Implication for Learning Indonesian Language in Junior School - Asep Muhyidin (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the use of lexical cohesion reiteration in Padang Kurusetra short story by Emha Ainun Najib. This research used a qualitative approach. The data taken is a lingual unit of sentences that has an lexical cohesion reiteration marker. The method used to collect data in this research is referred to reading. Data analysis in this study uses the cloze method. The results showed that there was a lexical cohesion reiteration in the Padang Kurusetra short story by Emha Ainun Najib. There was 17 repetition, 7 synonymy, 10 oppositions, and 1 hyponymy. The function of the four lexical cohesion reiteration is to provide coherence of words or phrases in each paragragp so that the understanding of the author will be same as the reader’s. Then, the results of this research can be implicated in Indonesia language instruction in junior high school.Keywords: Lexical cohesion reiteration, short story, Indonesian language intruction.